2017
DOI: 10.4103/jehp.jehp_172_16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of individual counseling program by a midwife on fear of childbirth in primiparous women

Abstract: INTRODUCTION:Fear of childbirth is a common problem in pregnant women, which in many cases leads to maternal requested cesarean. A midwife, as a responsible person, plays an important role in providing advice and giving care to mothers during pregnancy, delivery, and the postpartum period. The present study was conducted with the aim of determining the effect of individual counseling program by a midwife on fear of childbirth in primiparous women.MATERIALS AND METHODS:This clinical trial was conducted in 2015–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…In another study, the rate of general anxiety diminished moderately with six sessions of mindfulness (Guardino et al, 2014). A study reported the reduction of general pregnancy anxiety in a three-session intervention by a midwife (Andaroun et al, 2018). It is supposed that different reductions of general anxiety in various studies and the number of sessions may be related to the type of the therapy, the duration of the therapy, and the person conducting the psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the rate of general anxiety diminished moderately with six sessions of mindfulness (Guardino et al, 2014). A study reported the reduction of general pregnancy anxiety in a three-session intervention by a midwife (Andaroun et al, 2018). It is supposed that different reductions of general anxiety in various studies and the number of sessions may be related to the type of the therapy, the duration of the therapy, and the person conducting the psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that vulnerability in women during this period is associated with reduced selfcare during post-partum (1). The midwife is considered to play a significant role in post-partum transition (24), counseling and maternal care during pregnancy, childbirth, and post-partum (25), maintaining and improving maternal and infant health, providing favorable care, counseling, and teaching health to women, family and society (26). Therefore, the midwife should assess the women in terms of their risk factors, mental and physical health, and compatibility with post-partum conditions, and educate the appropriate preventative strategies and provide the necessary care (2).…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies examined other talking therapies (excluding CBT) delivered face-to-face (n = 11; Ahmadi et al, 2018;Andaroon, Kordi, Kimiaei, & Esmaeily, 2017;Halvorsen, Nerum, Sørlie, & Øian, 2010;Henriksen, Borgen, Risløkken, & Lukasse, 2018;Klabbers, Paarlberg, & Vingerhoets, 2018;Klabbers, Wijma, Paarlberg, Emons, & Vingerhoets, 2019;Larsson, Karlström, Rubertsson, & Hildingsson, 2015;Nerum, Halvorsen, Sørlie, & Øian, 2006;Ryding, Persson, Onell, & Kvist, 2003;Sjogren, 1998;Soltani, Eskandari, Khodakarami, Parsa, & Roshanaei, 2017;Sydsjö et al, 2012) or over the telephone (n = 1; Fenwick et al, 2015;Toohill et al, 2014;Toohill, Callander, Gamble, Creedy, & Fenwick, 2017;Turkstra et al, 2017). These approaches are a very diverse group, drawing on different theoretical frameworks including generic counselling, haptotherapy and psychotherapy.…”
Section: Other Talking Therapiesmentioning
confidence: 99%